2007
DOI: 10.1016/j.cub.2006.10.053
|View full text |Cite
|
Sign up to set email alerts
|

Direct Induction of Autophagy by Atg1 Inhibits Cell Growth and Induces Apoptotic Cell Death

Abstract: Our results reveal a central role for Atg1 in mounting a coordinated autophagic response and demonstrate that autophagy has the capacity to induce cell death. Furthermore, this work identifies autophagy as a critical mechanism by which inhibition of TOR signaling leads to reduced cell growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

52
732
10
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 655 publications
(797 citation statements)
references
References 47 publications
52
732
10
3
Order By: Relevance
“…Although cytoprotective and cytotoxic roles have been ascribed to ULK1's autophagic function, 21,23,46 our results provide evidence that ULK1 acts as a prodeath molecule in an Atg7-independent manner. In Drosophila, overexpression of Atg1 promotes cell death through an apoptotic pathway, 47 whereas in human osteosarcoma cells treated with camptothecin the p53-dependent upregulation of ULK1 potentiates cell death. 21 Our results indicate that ULK1 is one of several ATG proteins that induces cell death through autophagy-independent pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Although cytoprotective and cytotoxic roles have been ascribed to ULK1's autophagic function, 21,23,46 our results provide evidence that ULK1 acts as a prodeath molecule in an Atg7-independent manner. In Drosophila, overexpression of Atg1 promotes cell death through an apoptotic pathway, 47 whereas in human osteosarcoma cells treated with camptothecin the p53-dependent upregulation of ULK1 potentiates cell death. 21 Our results indicate that ULK1 is one of several ATG proteins that induces cell death through autophagy-independent pathways.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the disaccharide trehalose is an mTOR-independent activator of autophagy (30). The induction of autophagy occurs through a mechanism that involves the Atg1 kinase, which when overexpressed in Drosophila is sufficient to induce autophagy (31). In mammalian cells the Atg1 ortholog ULK1 also controls autophagy (32).…”
Section: Regulation Of Autophagymentioning
confidence: 99%
“…Neufeld and colleagues performed experiments to overexpress Atg1 in Drosophila and found that this was sufficient to increase autophagy, to inhibit cell growth and to induce cell death (31). However, while the death required that the autophagy signal from Atg1 be propagatedmutation of a downstream autophagy regulator, Atg8 blocked the Atg1-induced death-the actual mechanism of cell death appeared to be through apoptosis and was associated with increased caspase activity and blocked by a caspase inhibitor.…”
Section: Are Autophagic and Apoptotic Cell Death Different Facets Of mentioning
confidence: 99%
“…In Drosophila, enforced ATG1 expression induces excessive autophagy, resulting in apoptosis [16]. Similarly, destruction of the fly larval salivary gland involves massive autophagy and ATGs are required for this developmental cell death [17].…”
Section: Autophagy and Cell Fatementioning
confidence: 99%